Solar light-condensing sintering device and preparation method of solar cell device of solar light-condensing sintering device

By designing a solar light-concentrating sintering device, the metal oxide electron transport layer of perovskite solar cells is sintered at low temperature, which solves the energy consumption and environmental pollution caused by traditional high-temperature sintering, and achieves the reduction of battery preparation cost and performance improvement.

CN119468511APending Publication Date: 2025-02-18NINGBO UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411444179.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-16
Publication Date
2025-02-18

AI Technical Summary

Technical Problem

During the preparation of traditional perovskite solar cells, the high-temperature sintering of the metal oxide electron transport layer leads to high energy consumption and serious environmental pollution, and material unevenness and structural defects affect the battery performance and stability.

Method used

A solar-energy light-concentrating sintering device is designed, using a Fresnel lens to focus solar radiation, and perform low-temperature sintering of the metal oxide electron transport layer. Combined with a simple preparation method and a temperature detection system, the process is simplified and energy consumption is reduced.

Benefits of technology

It effectively reduces energy consumption and environmental pollution during traditional sintering, reduces the cost of battery preparation, improves the utilization efficiency of solar energy, and improves the uniformity of materials and structural stability.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119468511A_ABST
    Figure CN119468511A_ABST
Patent Text Reader

Abstract

The invention relates to a solar concentrating sintering device and a preparation method of a solar cell device, the solar concentrating sintering device comprises a sintering platform and a focusing module, the focusing module adopts a Fresnel lens, a lifting bracket is mounted below the sintering platform, and a mask plate for placing a sintering sample and a temperature detection system are mounted on the sintering platform; the preparation method comprises the following steps: sintering the metal oxide electron transport layer by a solar light-gathering sintering device; the sintered metal oxide electron transport layer is coated on the surface of the substrate; preparing a perovskite precursor solution, and coating the perovskite precursor solution on the metal oxide electron transport layer; preparing a hole transport layer by using anhydrous chlorobenzene; a silver layer having a thickness of 75 nm is thermally evaporated on the top of the device. The device is simple and reasonable in structure, firm and stable in assembly, simple in preparation method process, low in energy consumption, energy-saving, environment-friendly and low in cost, and large-scale production and commercialized popularization of the perovskite solar cell are facilitated.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of solar cell preparation, and relates to a solar energy concentration sintering device and a preparation method of a solar cell device thereof. Background Art

[0002] Perovskite solar cells have attracted much attention due to their high efficiency and low manufacturing cost, and are regarded as an important direction for the future utilization of solar energy. However, there are some drawbacks in the traditional preparation process of perovskite solar cells, especially in the sintering step of the metal oxide electron transport layer. In the traditional preparation method, the metal oxide electron transport layer usually needs to be sintered in a high-temperature furnace, which is not only energy-intensive but also has a certain impact on the environment. The use of high-temperature furnaces leads to significant energy consumption and increases production costs. In addition, the operation and maintenance of high-temperature furnaces also require additional resources and time, which limits the large-scale production and commercialization of perovskite solar cells. In addition, the traditional high-temperature sintering process may cause material inhomogeneity and structural defects, which may affect the performance and stability of solar cells. At the same time, the waste and emissions generated during the high-temperature sintering process may also pollute the environment, which is contrary to the current global promotion of green, low-carbon and sustainable development concepts.

[0003] Therefore, it is necessary to propose a new sintering device and preparation method to meet the needs of perovskite solar cell preparation while reducing energy consumption and lowering production costs. Summary of the invention

[0004] The first technical problem to be solved by the present invention is to provide a solar energy concentrating sintering device with a reasonable structure, firm and stable assembly, and the device has the characteristics of good sintering effect, low cost, and green environmental protection.

[0005] The second technical problem to be solved by the present invention is to provide a method for preparing a solar cell device, which uses the above-mentioned solar energy concentrating sintering device to sinter the metal oxide electron transport layer, has the characteristics of simple and reasonable process, low energy consumption, energy saving and environmental protection, and effectively reduces the preparation cost.

[0006] The technical solution adopted by the present invention to solve the above-mentioned first technical problem is: a solar concentrating sintering device, characterized in that it includes a sintering platform and a focusing module that concentrates solar radiation to the sintering platform, the focusing module adopts a Fresnel lens, the Fresnel lens is installed on a stainless steel frame, a lifting bracket that can lift and lower the sintering platform is installed under the sintering platform, and a mask for placing the sintering sample and a temperature detection system for real-time monitoring of temperature changes during the sintering process are installed on the sintering platform.

[0007] As an improvement, the stainless steel frame is installed on the bracket and can adjust the angle through a rotating mechanism according to the direction of sunlight. The lifting bracket is a cross-type lifting bracket. The sintering platform is fixed on the lifting bracket, and the sintering position is adjusted to the Fresnel lens focusing axial position through the lifting bracket.

[0008] Furthermore, the temperature detection system comprises a thermocouple thermometer probe; the mask is fixed at the middle position of the upper end surface of the sintering platform, and the upper end surface of the mask is provided with a plurality of grooves for placing the sintering samples.

[0009] Finally, the mask is square, the grooves are evenly distributed square grooves, and the size of the square grooves is customized according to actual conditions.

[0010] The technical solution adopted by the present invention to solve the above second technical problem is: a method for preparing a solar cell device, characterized in that: the structure of the solar cell device is substrate / metal oxide electron transport layer / perovskite light absorption layer / hole transport layer / Ag, and the specific preparation process is as follows:

[0011] 1) using any one of the above solar concentrating sintering devices to sinter the metal oxide electron transport layer;

[0012] 2) pre-treating the substrate, and then coating the metal oxide electron transport layer sintered in step 1) on the surface of the substrate;

[0013] 3) preparing a perovskite precursor solution, coating the perovskite precursor solution on the metal oxide electron transport layer, and then rotating the substrate in two steps: 1000±100rpm for 10±1s and 6000±600rpm for 30±3s; in the second step, 13s before the end of the spin coating, dripping 180±18μL of chlorobenzene in the center of the film, and washing the substrate with a dynamic solvent to obtain a perovskite light absorbing layer;

[0014] 4) preparing a hole transport layer using anhydrous chlorobenzene;

[0015] 5) Finally, a 75±5nm thick silver layer was thermally evaporated on top of the device to form the back contact.

[0016] Furthermore, the metal oxide electron transport layer in step 1) is an m-TiO2 layer, and the sintering process is: placing the metal oxide electron transport layer material in the mask on the upper end of the sintering platform, and then sintering it through the concentrated sunlight generated by the Fresnel lens, the sintering temperature is 500±50℃, and the sintering time is 60±5min.

[0017] Furthermore, the substrate in the step 2) is a FTO glass substrate, and the specific process of substrate pretreatment is: the substrate is washed with deionized water and ethanol in an ultrasonic bath for 15±2 minutes, dried with a hair dryer in the air, and then treated with ultraviolet ozone for 15±2 minutes; the metal oxide electron transport layer is coated on the surface of the substrate at a speed of 5000±500rpm, and the coating time is 30±5s.

[0018] Furthermore, the process for preparing the perovskite precursor solution in step 3) is as follows: 677.7±10 mg lead iodide, 216.7±10 mg FAI and 23.6±1 mg cesium chloride are dissolved in a mixed solvent of 800±10 μL DMF and 200±10 μL DMSO to prepare the perovskite precursor solution.

[0019] Furthermore, in step 4), the hole transport layer uses spiro-OMeTAD with a concentration of 72.3±5 mg / mL, doped with 29±1 μL 4-tBP and 18±1 μL Li-TFS / acetonitrile.

[0020] Finally, steps 2) to 5) are all prepared in a nitrogen environment.

[0021] Compared with the prior art, the advantages of the present invention are: using solar energy as a sintering energy source, designing a solar energy concentrating sintering device to sinter the metal oxide electron transport layer, reducing energy consumption and environmental pollution in the traditional sintering process, conforming to the development trend of green energy, effectively improving the utilization efficiency of solar energy, and reducing the cost of battery preparation. The device structure of the present invention is simple and reasonable, the assembly is firm and stable, the preparation method is simple, the energy consumption is low, and the energy saving and environmental protection are greatly reduced. At the same time, the cost is greatly reduced, and the dependence on traditional high-temperature furnaces is reduced, which provides more possibilities for the sintering of perovskite solar cells and other materials, and is conducive to the large-scale production and commercial promotion of perovskite solar cells. BRIEF DESCRIPTION OF THE DRAWINGS

[0022] Figure 1 is a schematic structural diagram of a solar energy concentrating sintering device provided in an embodiment of the present invention;

[0023] Figure 2 yes Figure 1 A partial enlarged schematic diagram of the sintering platform;

[0024] Figure 3 Figure a is a schematic diagram of the sintering process of the solar energy concentrating sintering device; Figure b is a physical image of the solar energy concentrating sintering device; Figure c is a partial enlarged view of the sintering platform in Figure b;

[0025] Figure 4The following are scanning electron microscope (SEM) images of m-TiO2 films prepared by different processes, where (a) is the treated m-TiO2 film, (b), (c), and (d) are m-TiO2 films sintered by concentrated sunlight for 20, 40, and 60 min, respectively, (e) is the m-TiO2 film sintered by a high temperature furnace for 60 min, and (f) is a schematic diagram of the working principle of PSC based on m-TiO2 layer;

[0026] Figure 5 (a) and (b) are photos of m-TiO2 films obtained by concentrated sunlight sintering and m-TiO2 films sintered in a high-temperature furnace, respectively; (c-d) are the test results of visible light transmittance and carbon content change of m-TiO2 films prepared by solar concentrated sintering at different times and m-TiO2 films prepared by sintering in a high-temperature furnace for 60 minutes. (e-h) are the conductivity test results, XRD results and locally enlarged XRD results of m-TiO2 films prepared by solar concentrated sintering at different times and m-TiO2 films prepared by sintering in a high-temperature furnace for 60 minutes, respectively.

[0027] Figure 6 (a) to (e) are the core-level XPS spectra of Ti 2p of m-TiO2 films prepared under different sintering conditions, and (f) is the Ti 2p spectra of m-TiO2 films prepared by solar concentrating sintering for different time periods and m-TiO2 films prepared by high-temperature furnace sintering for 60 min. 4+ Content comparison.

[0028] Figure 7 (a) to (e) are O1s nuclear photoelectron spectra of m-TiO2 films prepared under different sintering conditions, and (f) is the percentage change of hydroxyl content in the film under different processing conditions;

[0029] Figure 8 (a) to (e) are images of m-TiO2 films prepared under different sintering conditions measured by atomic force microscopy (AFM), and (f) is a roughness comparison diagram of m-TiO2 films prepared under different sintering conditions;

[0030] Fig. 9 (a) to (e) are SEM images of perovskite films grown on m-TiO2 layers prepared under different sintering conditions; (f) is the XRD result of perovskite films deposited on m-TiO2 under different sintering conditions;

[0031] Fig.10The cross-sectional structures of battery devices prepared under different sintering conditions, where a is a battery device prepared by concentrated sunlight sintering of m-TiO2, b is a battery device sintered in a conventional high-temperature furnace, and c-d are performance comparisons of battery devices prepared under different sintering conditions. (e-h) are the electrochemical impedance spectroscopy test, photovoltage decay and photocurrent decay test, and dark state JV test results of battery devices prepared under different sintering conditions. DETAILED DESCRIPTION

[0032] The present invention is further described in detail below with reference to the accompanying drawings.

[0033] like Figure 1 , 2 As shown, a solar concentrating sintering device includes a sintering platform 3 and a focusing module 2 for concentrating solar radiation on the sintering platform 3. The focusing module 2 uses a Fresnel lens, which is mounted on a stainless steel frame 1. A lifting bracket 4 for lifting and lowering the sintering platform is mounted below the sintering platform 3. A mask plate 7 for placing sintering samples and a temperature detection system 5 for real-time monitoring of temperature changes during the sintering process are mounted on the sintering platform 3. The stainless steel frame 1 is mounted on the bracket and can be adjusted in angle through a rotating mechanism according to the irradiation direction of sunlight. The use of a stainless steel frame can not only maintain the stability of the structure, but also facilitate outdoor installation and long-term use. The function of the Fresnel lens is to concentrate solar radiation to the center of the sintering platform 3 to provide the high temperature environment required during the sintering process.

[0034] The lifting bracket 4 is a cross-type lifting bracket, the sintering platform 3 is fixed on the lifting bracket 4, and the sintering position is adjusted by the lifting bracket 4 so that the sintering position is at the focusing axial position of the Fresnel lens. The temperature detection system 5 includes a thermocouple thermometer probe, which is used to monitor the temperature change during the sintering process in real time to ensure the accuracy and repeatability of the sintering process. In this way, the lifting bracket 4 and the temperature detection system 5 can realize accurate control of the heating temperature and the size of the heating area.

[0035] The mask plate 7 is fixed at the middle position of the upper end surface of the sintering platform 3, and the upper end surface of the mask plate 7 is provided with a plurality of grooves 8 for placing the sintered sample. The mask plate 7 of this embodiment is square, and the grooves 8 are 9 evenly distributed square grooves 8. The size of the square grooves 8 of this embodiment is 15 mm, and the size of the square grooves 8 can be customized and replaced according to actual conditions.

[0036] like Figures 3 to 10 As shown, a method for preparing a solar cell device, the structure of the solar cell device is substrate / metal oxide electron transport layer / perovskite light absorption layer / hole transport layer / Ag, and the specific preparation process is as follows:

[0037] 1) The above-mentioned solar energy concentrating sintering device is used to sinter the metal oxide electron transport layer; the metal oxide electron transport layer is an m-TiO2 layer, and the sintering process is: the metal oxide electron transport layer material is placed in the mask 7 at the upper end of the sintering platform 3, and then sintered by the concentrated sunlight generated by the Fresnel lens, the sintering temperature is 500±50℃, and the sintering time is 60±5min.

[0038] 2) Pre-treating the substrate, and then coating the metal oxide electron transport layer sintered in step 1) on the surface of the substrate; the substrate adopts an FTO glass substrate, and the specific process of the substrate pre-treatment is: washing the substrate with deionized water and ethanol in an ultrasonic bath for 15±2 minutes, drying it with a hair dryer in the air, and then treating it with ultraviolet ozone for 15±2 minutes; coating the metal oxide electron transport layer on the surface of the substrate at a speed of 5000±500rpm, and the coating time is 30±5s.

[0039] 3) Preparation of perovskite precursor solution: 677.7±10mg lead iodide, 216.7±10mg FAI and 23.6±1mg cesium chloride were dissolved in a mixed solvent of 800±10μL DMF and 200±10μL DMSO to prepare the perovskite precursor solution. The perovskite precursor solution was applied to the metal oxide electron transport layer, and then the substrate was rotated in two steps: 1000rpm for 10s and 6000rpm for 30s; in the second step, 13s before the end of the spin coating, 180μL chlorobenzene was dripped in the center of the film, and the substrate was washed with a dynamic solvent to obtain a perovskite light-absorbing layer;

[0040] 4) Preparation of a hole transport layer using anhydrous chlorobenzene: The hole transport layer uses spiro-OMeTAD with a concentration of 72.3±5 mg / mL, doped with 29±1 μL 4-tBP and 18±1 μL Li-TFS / acetonitrile.

[0041] 5) Finally, a 75nm thick layer of silver was thermally evaporated on top of the device to form the back contact.

[0042] Steps 2) to 5) are all prepared in a nitrogen environment.

[0043] The preparation method of the present invention is described in more detail below through experiments:

[0044] This experiment used conventional high temperature sintering at 500℃ (HT-TiO2) for 1 hour as the control group. The experimental group used concentrated sunlight sintering based on Fresnel lens (CSS-TiO2), and explored the optimal duration of CSS during the experiment. Different sintering times were set, namely 20min, 40min and 60min. Figure 4(a) is the untreated m-TiO2 film, (b) to (d) are concentrated sunlight sintering (CSS-TiO2), and the sintering time is 20min, 40min and 60min respectively; (e) is the m-TiO2 film sintered in a conventional furnace at high temperature for 1 hour.

[0045] The five m-TiO2 films prepared above were scanned and the scanning electron microscope (SEM) images were as follows: Figure 4 Shown Figure 4 f is a schematic diagram of the working principle of PSC based on m-TiO2 layer.

[0046] Figure 5 The following are photos of m-TiO2 films obtained by concentrated sunlight sintering and m-TiO2 films sintered in a furnace. It can be seen that they have similar obvious colors. It is preliminarily proved that the sintering effect of concentrated sunlight sintering is basically the same as that of slag furnace sintering. For PSC, an excellent m-TiO2 layer must have good transparency, acting as a window layer to allow visible light to pass through. Figure 5 (c) It can be seen that with the increase of CSS time, the absorption capacity of CSS-TiO2 film decreases, while the transparency increases. Energy dispersion (EDX) spectrum is shown in Figure 2. Figure 5 (d) shows that the carbon content in the film is significantly reduced after sintering for 20 min, which strongly indicates that the organic impurities in the m-TiO2 precursor layer are effectively removed. Figure 5 (e~h) are the conductivity test results, XRD results and locally enlarged XRD results of the m-TiO2 film prepared by solar concentrated sintering at different times and the m-TiO2 film prepared by high-temperature furnace sintering for 60 minutes.

[0047] Figure 6 X-ray photoelectron spectroscopy (XPS) was used to characterize the Ti 2p and O1s spectra of CSS-TiO2 and HT-TiO2 films. Figure 6 (a) to (e) show the core-level XPS spectra of Ti 2p of the corresponding films. The peaks at around 463 eV and 458.3 eV are the spin-orbit doublets of Ti 2p1 / 2 and Ti 2p3 / 2, respectively. After CSS annealing, the peaks of Ti 2p shift to higher energy regions. This means that the oxidation state of titanium increases because Ti 4+ Ti 3+ Has higher binding energy. Figure 6 (f) TiO2 films prepared by solar concentrating sintering for different time periods and m-TiO2 films prepared by high temperature furnace sintering for 60 min. 4+ Content comparison.

[0048] Figure 7(a)-(e) specifically show the O1s core-level photoelectron spectra of the corresponding m-TiO2 films. It can be observed that the peak at 529.4 eV corresponds to the Ti 3+ , while the peak at 530.3 eV corresponds to Ti 4+ After high temperature annealing, Ti 4+ The peak value of Ti gradually increases and the area is larger, indicating that 4+ This result is consistent with the change of the Ti 2p3 / 2 peak mentioned above. We believe that Ti 4+ The gradual increase of is a natural result because the sample is sintered in open air with sufficient oxygen to ensure sufficient oxygen partial pressure. The energy peak is located at 531.8 eV, corresponding to the hydroxyl (-OH) functional groups on the surface of the material. Figure 7 (f) Detailed display of the percentage change of hydroxyl content in the film under different processing conditions.

[0049] Figure 8 Atomic force microscopy (AFM) measurements show that Figure 8 (a)-(e) are scanning electron microscope (SEM) images. Figure 8 (f) is a roughness comparison. It can be seen that during the CSS sintering process, the surface roughness of the m-TiO2 film increases with the increase of sintering time. For the m-TiO2 film without any treatment, its surface is the smoothest and the roughness is the smallest, which is 13.1nm, and the number of mesopores is very small. This smoothness is due to the large amount of residual organic matter filled in the mesopores. As the sintering time increases, the organic components are photo-oxidized and volatilized, and the titanium dioxide nanocrystals are fused into larger grains through recrystallization, which increases the characteristic size and continuity of the pores and forms larger titanium dioxide grains protruding from the surface.

[0050] Fig. 9 SEM images of perovskite films grown on different m-TiO2 layers under different sintering conditions. Fig. 9 (a) shows a perovskite film grown on untreated m-TiO2 with blurred boundaries and underdeveloped grains. Fig. 9 (b)-(d) show the perovskite film grown on the m-TiO2 film treated with CSS for 20min, 40min, and 60min, respectively. With the increase of sintering time, the crystals become fuller and more compact, which helps to strengthen the internal bonding force of the crystals and improve the mechanical stability and durability of the material. This observation is consistent with the results of subsequent device stability tests. Fig. 9(f) is the XRD result of perovskite films deposited on m-TiO2 under different sintering conditions. In the upper right corner of the figure, the diffraction peak of the perovskite (110) plane is convenient for comparison. The results show that after CSS-60min treatment, the perovskite film deposited on m-TiO2 has the highest diffraction peak intensity, indicating better crystallinity and larger crystal size.

[0051] The performance of the solar cell device prepared by this embodiment is compared with that of the solar cell device prepared by conventional high temperature furnace sintering treatment. Fig.10 (a) is the cross-sectional structure of the solar cell device made of m-TiO2 by sunlight sintering. Fig.10 (b) is the cross-sectional structure of the battery device sintered in a conventional high-temperature furnace. The structures of the two battery devices are as follows: FTO / m-TiO2 / perovskite / spiro-OMeTAD / Ag. The device prepared using CSS technology showed the following parameters: Voc is 0.986V, Jsc is 23.68mA / cm 2 , FF is 74.21% and PCE is 17.69%. In contrast, the different sintering processes have negligible effects on Jsc. These results strongly confirm the potential of concentrated sunlight sintering as a viable alternative to traditional high-temperature furnace sintering methods, emphasizing its ability to improve device performance. The JV curves of the optimal devices prepared using different processes are shown in Figure 2. Fig.10 (c) Impedance test results Fig.10 (e) shows that the HT-60min and CSS-60min devices have higher resistance, which means lower recombination rate. The TPC results show that the carriers generated within the cell have faster transmission speeds and less recombination losses, which is consistent with the longer decay lifetime observed in the TPV measurements. The subsequent dark current test was performed under dark conditions, where the carriers within the device flow under the influence of the electric field. It is clear that the CSS-60min device exhibits a lower dark current. This result indicates that the battery has fewer internal defects, which enhances the battery's Voc and FF, and also contributes to the stability of the battery.

[0052] The present invention utilizes solar energy as sintering energy and designs a solar energy concentrating sintering device to sinter the metal oxide electron transport layer, which effectively reduces the energy consumption and environmental pollution in the traditional sintering process, conforms to the development trend of green energy, improves the utilization efficiency of solar energy, reduces the cost of battery preparation, and reduces the dependence on traditional high-temperature furnaces, providing more possibilities for the sintering of perovskite solar cells and other materials, and is conducive to the large-scale production and commercial promotion of perovskite solar cells.

[0053] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the technical principles of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.

Claims

1. A solar concentrating sintering device, characterized in that: It includes a sintering platform and a focusing module for concentrating solar radiation onto the sintering platform. The focusing module adopts a Fresnel lens, which is mounted on a stainless steel frame. A lifting bracket for lifting and lowering the sintering platform is installed under the sintering platform. A mask for placing sintering samples and a temperature detection system for real-time monitoring of temperature changes during the sintering process are installed on the sintering platform.

2. The solar concentrating sintering device according to claim 1, characterized in that: The stainless steel frame is installed on the bracket and can be adjusted in angle through a rotating mechanism according to the irradiation direction of sunlight. The lifting bracket is a cross-type lifting bracket. The sintering platform is fixed on the lifting bracket, and the sintering position is adjusted to the focusing axial position of the Fresnel lens through the lifting bracket.

3. The solar concentrating sintering device according to claim 1, characterized in that: The temperature detection system comprises a thermocouple thermometer probe; the mask is fixed at the middle position of the upper end surface of the sintering platform, and the upper end surface of the mask is provided with a plurality of grooves for placing sintering samples.

4. The solar concentrating sintering device according to claim 1, characterized in that: The mask is square, and the grooves are evenly distributed square grooves, and the size of the square grooves is customized according to actual conditions.

5. A method for preparing a solar cell device, characterized in that: The structure of the solar cell device is substrate / metal oxide electron transport layer / perovskite light absorption layer / hole transport layer / Ag, and the specific preparation process is as follows: 1) Using the solar energy concentrating sintering device described in any one of claims 1 to 4 to sinter the metal oxide electron transport layer; 2) pre-treating the substrate, and then coating the metal oxide electron transport layer sintered in step 1) on the surface of the substrate; 3) preparing a perovskite precursor solution, coating the perovskite precursor solution on the metal oxide electron transport layer, and then rotating the substrate in two steps: 1000±100rpm for 10±1s and 6000±600rpm for 30±3s; in the second step, 13s before the end of the spin coating, dripping 180±18μL of chlorobenzene in the center of the film, and washing the substrate with a dynamic solvent to obtain a perovskite light absorbing layer; 4) preparing a hole transport layer using anhydrous chlorobenzene; 5) Finally, a 75±5nm thick silver layer was thermally evaporated on top of the device to form the back contact.

6. The preparation method according to claim 5, characterized in that: The metal oxide electron transport layer in step 1) is an m-TiO2 layer, and the sintering process is: placing the metal oxide electron transport layer material in a mask on the upper end of a sintering platform, and then sintering it by focusing the concentrated sunlight generated by a Fresnel lens, the sintering temperature is 500±50°C, and the sintering time is 60±5min.

7. The preparation method according to claim 5, characterized in that: The substrate in the step 2) is an FTO glass substrate, and the specific process of substrate pretreatment is: the substrate is washed with deionized water and ethanol in an ultrasonic bath for 15±2 minutes, dried with a hair dryer in the air, and then treated with ultraviolet ozone for 15±2 minutes; the metal oxide electron transport layer is coated on the surface of the substrate at a speed of 5000±500rpm, and the coating time is 30±5s.

8. The preparation method according to claim 5, characterized in that: The process for preparing the perovskite precursor solution in step 3) is as follows: 677.7±10 mg of lead iodide, 216.7±10 mg of FAI and 23.6±1 mg of cesium chloride are dissolved in a mixed solvent of 800±10 μL DMF and 200±10 μL DMSO to prepare the perovskite precursor solution.

9. The preparation method according to claim 5, characterized in that: In the step 4), the hole transport layer uses spiro-OMeTAD with a concentration of 72.3±5 mg / mL, doped with 29±1 μL 4-tBP and 18±1 μL Li-TFS / acetonitrile.

10. The preparation method according to claim 5, characterized in that: The steps 2) to 5) are all prepared in a nitrogen environment.